MAPPING THE FUTURE OF EDUCATION: A BIBLIOMETRIC ANALYSIS OF DESIGN THINKING, CREATIVE METACOGNITION AND NEUROSCIENCE APPROACHES - Zainol, Noranyza; Ab Wahid, Hariyaty (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The rapid transformation of global education in the era of the Fifth Industrial Revolution (5IR) highlights the need for innovative and human-centered learning paradigms that integrate design thinking, creative metacognition, and neuroscience. While each of these domains has gained scholarly attention, there remains a gap in understanding how they collectively shape the evolution of future education. This study aims to map the intellectual landscape, research trends, and thematic connections among these three key areas. Using a bibliometric approach, data were retrieved from the Scopus database through advanced searching with the keywords "Design Thinking," "Creative Metacognition," and "Neuroscience," resulting in a total of 1,492 documents. The dataset was refined and standardized using Open Refine to ensure data consistency and accuracy. Statistical and graphical analyses were conducted using the Scopus Analyzer to examine publication growth, prolific authors, leading countries, and source distribution, while VOS viewer software was used to visualize co-authorship networks, keyword co-occurrence, and citation relationships. The results show a significant increase in publication output over the past decade, with the United States, the United Kingdom, and China emerging as leading contributors. Four major thematic clusters were identified the design-driven learning innovation, neuro-cognitive approaches to creativity, interdisciplinary education, and technology-enhanced pedagogy and indicating strong research convergence across these domains. These findings reveal that future educational development is shifting toward a 5IR framework that emphasizes the synergy between human intelligence and advanced technology. In conclusion, this study contributes to the growing body of knowledge by illustrating how the integration of design thinking, creative metacognition, and neuroscience can support adaptive, empathetic, and innovation-driven education systems aligned with the transformative goals of the Fifth Industrial Revolution.